Acute pancreatitis and acute respiratory distress syndrome complicating dengue haemorrhagic fever. (15th November 2011) - Agrawal, Avinash; Jain, Nirdesh; Gutch, Manish; Shankar, Amit
Abstract : Dengue infection is now known to present with wide spectrum of complications. Isolated cases of acute pancreatitis complicating dengue haemorrhagic fever have been reported in literature. Here the authors report a case of dengue haemorrhagic fever that develops acute pancreatitis and presented with acute onset of breathlessness, which then progressed to full-blown acute respiratory distress syndrome. To our knowledge, this is the first reported case of dengue haemorrhagic fever complicated with acute pancreatitis and acute respiratory distress syndrome.